THE EFFECT OF UNEMPLOYMENT ON THE ECONOMIC SECURITY OF THE COUNTRY AND MEASURES TO PREVENT IT - Safarov G’iyosiddin Abdullayevich; Zokirjon Bahodirov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, employment indicators and unemployment indicators in the Republic of Uzbekistan are highlighted based on the information of the State Statistics Committee of the Republic of Uzbekistan. In addition, this article includes the sets of measures taken by our government to reduce the unemployment rate and increase the employment rate in the country.